Drosophila Myc Interacts with Host Cell Factor (dHCF) to Activate Transcription and Control Growth. - Furrer, M.; Balbi, M.; Albarca-Aguilera, M.; Gallant, M.; Herr, W.; Gallant, P. (Journal of Biological Chemistry, 2010)
The Myc proto-oncoproteins are transcription factors that recognize numerous target genes through hexameric DNA sequences called E-boxes. The mechanism by which they then activate the expression of these targets is still under debate. Here, we use an RNAi screen in Drosophila S2 cells to identify Drosophila host cell factor (dHCF) as a novel co-factor for Myc that is functionally required for the activation of a Myc-dependent reporter construct. dHCF is also essential for the full activation of endogenous Myc target genes in S2 cells, and for the ability of Myc to promote growth in vivo. Myc and dHCF physically interact, and they colocalize on common target genes. Furthermore, down-regulation of dHCF-associated histone acetyltransferase and histone methyltransferase complexes in vivo interferes with the Myc biological activities. We therefore propose that dHCF recruits such chromatin-modifying complexes and thereby contributes to the expression of Myc targets and hence to the execution of Myc biological activities.